COMMUNITY EMPOWERMENT THROUGH THE FORMATION OF THE PANEMBONGAN TOURISM TOURISM MOVEMENT TOURISM IN TEMBONG VILLAGE, GARAWANGI DISTRICT, KUNINGAN REGENCY - Lia Muliawaty; R. Taqwaty Firdausijah; Mira Rosana; Kamal Alamsyah (LPM Universitas Pasundan, 2020)
The presence of Bukit Panembongan nature tourism is inseparable from the surrounding community and the youth of Karang Taruna in Tembong Village who explore the potential possessed by one of the hill areas located in the Panembongan Village. Bukit Panembongan Nature Tourism which is located in Tembong Village, Garawangi District, Kuningan Regency was opened to the public on March 28, 2015. The area of ​​land reaches 5ha but the effective land is around 3ha. Panembongan Hill natural attractions start open at 08.00 WIB until 17.00 WIB. Based on the conditions in the field can be found the following problems: the dissolution of the group of tourism activists in the Panembongan hill destination. Partners still have not sought to increase tourism service interest at the village / sub-district level by involving tourism service entrepreneurs in order to support the success of the K3 program, Partners still do not have the ability to organize funds seeking tourism activists (Kompepar) through the sale of souvenirs, the establishment of cooperatives, kiosks and so on. After the implementation team discussed with the local authorities , the activity implementation team determined the solution priority, namely the problem related to the formation of a tourism driving group, coordinating with the management of this tourism object was the result of collaboration between Perhutani KPH Kuningan with Forest Village Community Institutions (LMDH) and Tembong Village with a system of Community-Based Forest Management (PHBM), which is managed 90% by Perhutani and 10% by the Village. In connection with the problem, this activity aims to help resolve some of the problems faced by Partners as previously stated. The implementation method used in this activity is by lecturing and training. The conclusion of this activity is that the assistance provided by the Implementation Team can be understood by partners and is in accordance with the planned activities and priorities. Suggestions that can be delivered are: the formation of a tourism driving group, holding a meeting with the Ministry of Forestry and Forest Village Community Institutions (LMDH) and the Village Head to resolve the Joint Forest Management System pattern.